Survey Study on the Increase of Arabic Learning Due to Smartphones - Salam, Muhamad Yusuf; Xavier, Murphy; Elliot, McCarty (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The Covid-19 pandemic is growing and spreading in various countries, changing various fields of people's lives, especially in Indonesia for some time. Purpose. The purpose of this observation is to find out the use of smartphones for students of public madarasah tsanawiyah (mtsn) 11 tanah datar when studying online. this observation is through a quantitative approach through a survey study method and selecting a sample by randomly determining 10 sources who live in the dormitory, 7th grade mtsn 11 tanah datar students have given questionnaire answers using Google from. Method. The research tool was adapted from several writings, the tool made 5 questions. Results. The results of the observation found that there were 7 people who had their own smartphones and 3 students used their parents' smartphones, relatives and other people in online learning, the time used to study via smartphones was between 5 to 6 hours. mtsn 11 flatland students using smartphones are classified as good categories in learning, doing and collecting assignments. So that students are able to discuss with their friends and all feel satisfied in using smartphones in online learning activities. Conclusion. suggestions for further researchers to use attitude variables, behavior and the impact of using smartphones for mtsn 11 flatland students who have their own smartphones.